Host Plant Mediated the Effect of Phosphorus on the Growth of External Hyphae of Gigaspora margarita - AGUS ROHYADI (Microbiology Indonesia, 2007)
The effect of soil phosphorus (P) administered to the host plant on the growth of external hyphae of Gigaspora margarita was investigated in a glasshouse experiment using pots divided into three compartments i.e. one for donor plants (DPC), one for external fungal hyphae (EHC) and one for receiver plants (RPC) respectively. The DPC was filled with a sterilized soil/sand mix previously set up to have 5, 16 or 26 mg Bray-1 P kg-1 soil (P1, P2,or P3; categorized as low, intermediate or high level of P-availability) at pH 5.3 and inoculated with and without the fungal inoculums, while the RPC was filled with P3 without inoculation. Two pre-germinated seeds of cowpea were then grown there for 2 weeks before filling the EHC with the original sterilized soil/sand mix having pH 4.6 and 12 mg Al3+ kg-1 soil. These plants were harvested after further grown for 4-8 weeks. P fertilizer induced different growth conditions of host plants, which could control the production of external hyphae by the fungal partner. In supporting G. margarita to develop an optimum extent of external hyphae in acidic soils with a toxic level of Al3+, cowpea plants required soil P availabilities at about the intermediate level.